Pengaruh Model Pembelajaran Role Playing dan Jigsaw terhadap Hasil Belajar IPS Ditinjau dari Motivasi Belajar - Rokhmad Riyadi; Retno Winarni; Ary Purwantiningsih (Syntax Corporation, 2023)
This research aims to determine the difference in the influence of the cooperative learning model Role Playing & Jigsaw methode on Social Science Major (IPS) learning result, differences in the influence of students who have high, middle, and low learning motivation on IPS learning result, and is there any interaction between learning models and learning motivation of students on Social Science Major (IPS) learning result. This research used 2*3 factorial design. Sampling is taken by purposive sampling technique. Sample of this research is student of SDIP Al Madinah Nogosari 5th grade and SDIP Al Madinah Cepogo 5th grade. The two population samples were then tested for prerequisite analysis through the normality test with the Kolmogorov-Smirnov test, the homogeneity test with Levene's test, and the balance test with the independent sample t-test. The research was continued by identifying the learning motivation of the students in the sample through a questionnaire instrument that had been tested for validity and reliability, and validated by experts. The questionnaire was made with a Likert scale of 1-4 with the results of the identification of learning motivation. Learning outcomes are obtained with test instruments that have been tested for validity, reliability, difficulty, and discriminating power, and validated by experts. Hypothesis testing was carried out using a two-way ANOVA and further testing using the Scheffe’s method using the SPSS Statistic 26 application. The results of the research showed; 1) There are no difference in the influence of the Role Playing learning model & Jigsaw on Social Science Major (IPS) learning result.; 2) There are differences in the influence of students who have high learning motivation, middle learning motivation, and low learning motivation on IPS learning result.; 3) There are no interaction of learning models and learning motivatin of students on IPS learning result.